Correlation of Density and Water Quality to Cortisol of Cantang Grouper Fish (Epinephelus fuscoguttatus X Epinephelus lanceolatus) in Floating Net Cages - Laksmi Sulmartiwi; Bintang Eka Nugraha Satia Aditama; Isnatul Umu Shohifah; Alfian Rahmadhani Satria Hani Saputra (Journal of Aquaculture and Fish Health, 2022)
Cantang grouper is a hybrid resulting from crosses between female tiger grouper (E. fuscoguttatus) and male kertang grouper (E. lanceolatus). Cultivation with floating net cages is one of the attempts made to cultivate cantang grouper fish. Problems that arise are the non-uniformity of the size of the fish when harvesting, this problem can lead to a decrease in selling prices and maintenance that tends to be longer. Metabolic disorders in living beings can be caused due to physiological stress and one of the causes can arise from water quality. Water quality is closely related to feeding and stocking density because the increase in feed and stocking density can affect the accumulation of feces to stress which causes slow growth. This study was conducted to find out the influence of density and water quality factors that play the most important role in the stress of cantang grouper fish based on indicators of cortisol levels. Cortisol testing is performed using the elisa method with Bioassay Technology Laboratory E0014Fi kit type. Data are processed using multiple linear regression test analysis that serves to determine the relationship and influence of the free variable (independent) X on non-free variables (dependent) Y. Regression analysis is used to determine the relationship between factors that are causal relationships. After the regression test, then the Analysis of Variance (ANNOVA) test is conducted, to find out the difference and influence of dependent parameters with significantly independent. There is a strong influence and correlation between water quality factors simultaneously to the cortisol levels of cantang grouper fish in floating nets, as can be seen from the R value of 0.546. The most influential water quality factor was nitrite with an effect of 19.7%. The next most significant water quality factor was ammonia with an effect of 37.1%. The indicated cortisol value can be known that fish are not in a state of stress due to increased NO2 and NH3. Density has no significant effect on cortisol because of its significance value above (p>0.05).